Debromination of Hexabromocyclododecane by Anaerobic Consortium and Characterization of Functional Bacteria - Peng, Xingxing; Wei, Dongyang; Huang, Qiyuan; Jia, Xiaoshan (Frontiers in Microbiology, 2018)
A microbial consortium which can efficiently remove HBCD under anaerobic condition have been successfully enriched over 300 days. Under the optimal conditions, the degradation efficiency was 92.4% removal after treatment of 12 days with original addition of 500 μg/L HBCD, yielding 321.7 μg/L bromide in total as well. A typical debromination product, dibromocyclododecadiene (DBCD), was detected during the degradation process. The debromination profiles of three main HBCD diastereomers fitted well with first-order model (R2: 0.96-0.99), with the rate constants ranging from 1.3×10-1 to 1.9×10-1. The microbial community analysis by high throughput sequencing showed that the composition of the microbial communities varied dynamically with time and the population of functional bacteria increase sharply after enrichment. The population of Bacteroidetes increased from 5% to 47%. And some bacteria which are relatively minority in population at the beginning, such as Azospira oryzae (OTU2), Microbacterium (OTU13), and Achromobacter insolitus (OTU 39) increased more than 22 times after enrichment (from 0.5% to 13%, 12% and 11%, respectively). However, no reported dehalogenating bacteria were found after enrichment. And the contribution for debromination may come from new dehalogenating bacteria. All in all, the present study provided in-depth information on anaerobic microbial communities for HBCD removal by debromination.